Vegetation analysis of tree communities at some forest patches in North Sulawesi, Indonesia - MUSTAID SIREGAR; HENDRA HELMANTO; SRI ULIE RAKHMAWATI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Siregar M, Helmanto H, Rakhmawati SU. 2019. Vegetation analysis of tree communities at some forest patches in North Sulawesi, Indonesia. Biodiversitas 20: 643-655. Deforestation has caused a decline in forest area in Indonesia. Now natural forests is left in the conservation areas while those outside conservation areas are narrow and fragmented. This study aims to analyze forest vegetation and conservation status of the species of trees in some forest patches in North Sulawesi. Diversity, structure and type of tree communities at five forest patches, namely in the villages of Bukaka, Garini and Lambak in East Bolaang Mongondow District, and Soyowan and Basaan villages in Southeast Minahasa District, North Sulawesi Province were studied using a point center quarter method. The total number of tree species (dbh ? 10 cm) across five patches is 84 species. The highest number of species is in Garini (37 species), followed by Lambak (25 species), Soyowan (19 species), Bukaka (10 species) and Basaan (7 species). The species diversity index also shows the same pattern with such species richness, but the dominance index demonstrates opposite trend. The highest evenness index (E) is found in Bukaka (E = 0.9524), followed by Soyowan (E = 0.9061), Garini (E = 0.7873), Basaan (E = 0.7809) and Lambak (E = 0.7099). The most important tree species based on the Species Important Value (SIV) in Bukaka is Ficus sp. (SIV = 52.17), in Garini is Octomeles sumatrana (SIV = 25.73), in Lambak is Boehmeria cylindrica (SIV = 65.03), both in Basaan and Soyowan is Dracontomelon dao with SIV of 96.87 and 46.46 respectively. The beta diversity analyzed based on species similarity index of Jaccard and Whittaker 's index shows a relatively large change in species composition from one location to another. The family of Moraceae, Malvaceae, Anacardiaceae, Annonaceae and Lauraceae are listed as the widest family with a relatively high population. The highest tree density is found in Bukaka (721 trees ha-1), followed by Lambak (482 trees ha-1), Basaan (439 trees ha-1), Garini (292 trees ha-1) and Soyowan (164 trees ha-1). The highest basal area is also found in Garini (53.59 m2 ha-1), followed by Basaan (51.62 m2 ha-1), Lambak (30.74 m2 ha-1), Soyowan (25.13 m2 ha-1) and Bukaka (20.98 m2 ha-1). The results of Cluster analysis using data of species abundance indicate that the five research locations tend to form two types of tree communities. The first community consists of Garini, Soyowan, Lambak and Bukaka, while the second community is represented only by Basaan.